Determinants of Domestic Tourism Demand in Indonesia - Tantowi, Akhmad (Jurnal Ilmu Ekonomi Terapan, 2022)
Domestic tourists have an essential role in the development of tourism in Indonesia. Knowledge of the variables that cause domestic tourists to travel is essential as one step to driving national tourism. This study aims to identify the economic variables that affect the travel of domestic tourists. The impact of changes in income, fuel prices, and the exchange rate of Rupiah per the US dollar will be estimated and tested. Dummy variables are also used to represent the Covid-19 pandemic in 2020. Multiple regression models will be used to analyze the relationship and influence of these variables on domestic tourists travelling using time series data for the period 2001-2020. An important finding in this study is the significance of income and fuel prices variables. It shows that income and transportation costs are the determining factors for domestic tourists travelling in Indonesia. Another finding is that the Covid-19 pandemic in 2020 caused a decrease in domestic tourist travel.